Paradoxical Effect of Aspirin. (20th October 2011) - Doutremepuich, Christian; Aguejouf, Omar; Desplat, Vanessa; Eizayaga, Francisco X.
Abstract : Low-dose aspirin is an important therapeutic option in the secondary prevention of myocardial infarction (MI) and ischemic stroke, basedon its unique cost-effectiveness and widespread availability. In addition, based on the results of a number of large studies, aspirin is also widely used in the primary prevention of MI. This paper provides an update of the available data to offer greater clarity regarding the risks of aspirin with respect to hemorrhagic stroke. In the secondary prevention of cardiovascular, cerebrovascular, and ischemic events, the evidence supports that the benefits of aspirin treatment significantly outweigh the risk of a major hemorrhage. When considering whether aspirin is appropriate, the absolute therapeutic cardiovascular benefits of aspirin must be balanced with the possible risks associated with its use, being hemorrhagic stroke. Regarding these clinical facts, normal, COX 1 −/−, and COX 2 −/− mice were treated with a wide range of doses of aspirin and studied by induced hemorrhagic time. The results outlined three major conclusions: high doses of aspirin induce hemorrhage, while low doses of aspirin do not. In the absence of COX 1, ultra low doses of aspirin produce an antihemorrhagic effect not observed with intermediate doses. The absence of COX 2 induced a hemorrhagic effect that needs further research, probably originated in compensatory phenomena.